The more the merrier? Chinese government R&D subsidies, dependence, and firm innovation performance. Issue 2 (22nd April 2021) - Yi, Jingtao; Murphree, Michael; Meng, Shuang; Li, Sali
Abstract: With the understanding that innovation and high technology industries are essential for sustained economic development, government R&D subsidies have become ubiquitous. However, existing studies on the impact of R&D subsidies have found mixed or conflicting results. Insights from resource dependence theory (RDT) and the Attention‐Based View (ABV) help account for these discrepancies. This study of Chinese high technology firms using the Innovation‐Oriented Firms Database from the Ministry of Science and Technology, finds an inverted U‐shaped relationship between R&D subsidies and innovation performance. The article shows that high government resource dependency, expressed through high percentage of R&D spending coming from government subsidies, diverts attention resources in recipient firms and results in declining innovation performance. The article then tests the impacts of different managerial responses on the dependency‐innovation relationship and find that technology alliances and employee feedback systems mitigate these negative effects. These findings have implications for government innovation policies and firm‐level responses to those policies: government subsidy policies have limits to their effectiveness and firms have strategic options for capitalizing on government resources without sacrificing innovativeness.